Revisión sistemática de las especies del género Bryconamericus (Teleostei: Characidae) de Centroamérica - Román-Valencia, César (2002)
A systematic revision of the fish genus Bryconamericus from Central America was done based in museum collections (UCR, STRI, BMNH, USNM, UMMZ) and samples collected by the author in Panama. Five valid species are recognized: B. bayano, B. emperador, B. gonzalezoi sp. nov. B. scleroparius and B. terrabensis; B. ricae is synonyms of B. scleroparius. Moreover, B. scleroparius and B. terrabensis were redescribed with fresh material and the lectotype of B. scleroparius was designated. Bryconamericus baudoensis, B. ortholepis, B. scopiferus (from western of Colombia), B. cascajalensis and B. zeteki (from Central America) are synonyms of B. emperador.